Ol' Clip-Clop : a ghost story - McKissack, Pat, 1944-2017 (Holiday House, 2013)
One October night in 1745, John Leep, a mean and stingy lawyer, sets out to evict a widow from one of his rental houses and is followed by a ghostly rider.